Generational Gender Stereotype (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Gender stereotypes are societal beliefs about how men and women should behave, think, and feel, leading to expectations and limitations based on their gender. These stereotypes are learned from a young age through family, media, and religion. They affect various aspects of life, including behavior, career choices, emotional expression, domestic roles, and appearance. This quantitative study utilized descriptive cross-sectional design which was participated by 311 respondents coming from Generation X, Y and Z. The researcher used weighted mean and standard deviation to analyze the level of favorability of gender stereotypes, while analysis of variance was used to identify significant differences among the three generations. This study revealed that there is a diminishing favorability towards gender stereotypes, indicating that people are becoming more egalitarian and considerate towards people regardless of gender. In addition, the respondents perceived that their personal characteristics moderately influence their perception towards gender stereotypes, shaping individuals' beliefs about societal expectations and their own behavior in relation to gender stereotypes, highlighting the nuanced interplay between individual traits and societal perceptions. The findings further emphasize that the Generation Y and Generation Z significantly differ in their attitudes towards gender stereotypes wherein the older generation tend to hold into these existing gender stereotypes, while the younger generation manifests their intent to break these stereotypes. The findings suggest a shifting societal attitude away from gender stereotypes, influenced moderately by personal traits, with notable generational differences highlighting a trend toward challenging traditional norms. The researchers came up with an audio-visual material to inform and educate people about the existing gender stereotypes and how they can break free from this to make themselves more empowered. Further studies can be done to capture the perceptions of generations older than Generation X or younger than Generation Z.
Keywords: generational stereotypes; gender stereotypes; personal characteristics